Influence of Hybrid Strategy on Small & Micro Enterprises (SMES) Performance: A Survey of Electronics Firms in Machakos Town, Machakos County, Kenya - Njoroge, Reuben Kimani; Arasa, Robert; Nganu, Margaret (My University, 2022)
The purpose of this study was to investigate influence of hybrid strategy on the performance of Small & Micro Enterprises (SMEs). This study focused electronics firms in Machakos Town, Machakos County, Kenya. A mixed research design was employed, where qualitative and quantitative data was collected and used. The target population comprised of all the 40 electronics outlets obtained as per the record of Machakos county Single Business Permit licensing office. The study respondents were 40 managers or owners drawn from the electronic retail shops in Machakos town CBD and residential estates. The questionnaire was the main data collection instrument. A pilot test was conducted to provide proxy data for selection of a probability sample and detect weaknesses in design and instrumentation. A multiple regression analysis was employed to establish the nature and magnitude of the relationship between the hybrid competitive strategy and performance of electronics SMEs. The study findings established that key success factors for the implementation of hybrid strategies are innovative strength, close orientation towards customer needs and organizational learning. The study findings indicates that adoption of singular generic strategy is insufficient in today’s competitive and dynamic market environments. Increase in competition, changing products cost factor, effects of globalization as well as changing customer expectations require firms to adopt a multidimensional strategic approach. Hybrid strategy that integrates cost and differentiation advantages represents a way for firms to respond to these changes in the competitive environment in a more flexible and effective approach and hence remain competitive.
Keywords: Customized product; Hybrid strategy; Small & Micro Enterprises; Superior customer